Preparation and photocatalytic property of Cu2O-TiO2 composite nanotube arrays film by the anodic oxidation - Ding, Qi; Chen, Suiyuan; Chen, Dongni; Liang, Jing; Liu, Changsheng (Surfaces and interfaces, 2016)
In the experiment, order anode oxidation TiO2 nanotube arrays (TNTs) film was prepared and achieved Cu electrolytic deposition synchronously in the electrolyte of NH4F, ethylene glycol and CuNO3 by periodic reverse voltage pulsed power. With the concentration of Cu(NO)2·3H2O and reverse voltage changing, the loading condition of Cu compound in the TNTs can also be changed. The photocatalytic performance of TNTs film and Cu2O-TNTs film after annealing at 450℃ were studied by degrading methylene blue (MB) under the condition of ultraviolet light. The morphology, structure, optical property were studied by means of SEM, EDS, XRD, XPS, photoluminescence spectroscopy (PL) and ultraviolet-visible diffuse reflection spectrum (UV-vis DRS). The results show that Cu loaded had no influence to morphology of the nanotubes, and the optical property of TNTs can be further improved after loading Cu by narrowing the band gap of TiO2 about 0.22 and decreasing the recombination rate of photoelectrons and holes. When the addition concentration of Cu2O-TNTs in the MB solution was 0.25cm2/mL, the degradation rate reached 72.63% from 43.45%. When increased concentration to 0.75cm2/mL, the degradation rate of MB reached 96.79%. The photocatalytic performance of Cu2O-TNTs film prepared by using single-step anodic method performed well under ultraviolet light.